PENGARUH DIABETIC SELF-MANAGEMENT EDUCATION (DSME) TERHADAP KEPATUHAN PENGOBATAN PADA PASIEN DIABETES MELITUS TIPE 2 - Rissa, Mexsi Mutia (Indonesian Journal of Pharmaceutical and Clinical Research, 2025)
Diabetes mellitus is a degenerative disease and remains among the top ten non-communicable diseases in Indonesia. High medication adherence plays a critical role in improving the quality of life of patients with type 2 diabetes mellitus. Pharmacists have a strategic role as educators in enhancing medication adherence through educational interventions, such as Diabetes Self-Management Education (DSME). This study aimed to analyze the effect of DSME on medication adherence among patients with type 2 diabetes mellitus at Bambanglipuro Primary Health Center, Bantul. This study employed a quasi-experimental design with a pre-test and post-test two-group design. The respondents were patients with type 2 diabetes mellitus who participated in the Prolanis program and met the inclusion criteria. Data were collected using a medication adherence questionnaire. Data analysis was performed using SPSS software with the Mann–Whitney U test after the intervention was administered. The results showed a p-value > 0.05, indicating that DSME had no significant effect on medication adherence among patients with type 2 diabetes mellitus at Bambanglipuro Primary Health Center, Bantul.